CAN IMPRESSION MANAGEMENT MODERATE THE RELATIONSHIP BETWEEN FINANCIAL PERFORMANCE AND COST OF EQUITY? - Santoso, Arif; Rahayu, Selvia; Sari, Puji Novita (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2024)
Stock market financing access plays an important role in sustainable business resilience and financial performance. In the Covid-19 pandemic, the banking sector has the potential to bear high equity costs commensurate with the risk. Impression management as a corporate communication strategy can maintain shareholder perception of corporate risk. The study aims to examine the effect of impression management in moderating the relationship between financial performance and cost of equity. The study consists of 228 bank-year observations on the Southeast Asian stock exchanges for 2020-2022. Data was obtained from the Annual Report, Integrated Report, and Form 56-1 One Report. This study examines separate companies that use one-tier and two-tier board systems. The findings indicate that improvements in financial performance had a negative impact on equity costs in Indonesia but a positive impact in Thailand, Singapore, Malaysia, and the Philippines. ROA and ROE only had a beneficial influence on Indonesia. The independent Board’s relationship to the cost of equity was not demonstrated. This study supports the idea that impression management improves the relationship between pandemic-related changes in financial performance and the cost of equity. The practical implications are that companies with negative changes in performance that also have proper impression management can attract investors with lower equity costs.